W sprawie pojęcia wyznaniowej żydowskiej osoby prawnej. Uwagi na tle wyroku Sądu Najwyższego z 9 lutego 2007 r., sygn. III CSK 411/06 - Borecki, Paweł (Studia Prawa Publicznego, 2020)
In its judgment of February 9, 2007 (Ref. No. III CSK 411/06), the Supreme Court formulated a narrow interpretation of the concept of a Jewish religious legal entity based on a formal criterion. In practice, the position of the Court has limited on a permanent basis the reprivatization of real estate to the benefit of Jewish communities and the Association of Communes. This reprivatization has been conducted in a narrow scope for over twenty years by the Regulatory Commission for Jewish Religious Communities. The restrictive interpretation that was adopted for the concept of a Jewish religious legal entity is inconsistent with the principle of correct legislation, with the principle of public trust in the state and its law, and in fact with the principle of social justice. Jewish religious communities in a number of areas are treated worse than the largest or oldest Christian churches. This applies in particular to the issue of membership of Jewish religious communities, tax matters or religious foundations. In addition, the interpretation of the Supreme Court does not take into account the historical forms of the organization of Judaism in Poland. On the other hand, the interpretation adopted on a consensus basis by the Regulatory Commission for Jewish Religious Communities in June 1999 is correct. It is functional. The Supreme Court should weigh constitutional principles and opt for this functional interpretation, instead of adopting a formal interpretation.